To determine whether \( x + 2 \) is a factor of the polynomial \( x^3 - 3x + 2 \), we can use the Factor Theorem. According to the Factor Theorem, \( x + c \) is a factor of a polynomial \( f(x) \) if and only if \( f(-c) = 0 \).
In this case, since we have \( x + 2 \), we set \( c = -2 \). Now, we will evaluate the polynomial \( f(x) = x^3 - 3x + 2 \) at \( x = -2 \):
\[ f(-2) = (-2)^3 - 3(-2) + 2 \] \[ = -8 + 6 + 2 \] \[ = -8 + 8 \] \[ = 0 \]
Since \( f(-2) = 0 \), according to the Factor Theorem, \( x + 2 \) is indeed a factor of the polynomial \( x^3 - 3x + 2 \).
Thus, James is correct, and Susan is incorrect. The work shows that \( x + 2 \) divides \( x^3 - 3x + 2 \) without a remainder, confirming it is a factor.